2011
DOI: 10.3329/jsr.v4i1.7598
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Chemical Components Involved in Germination Process of Rice Variety Jhapra

Abstract: Notice of withdrawal/removalThe article “Analysis of Chemical Components Involved in Germination Process of Rice Variety Jhapra” which appeared in J. Sci. Res. 4 (1), 251-262 (2012) has now been removed from journal’s website for violation of journal’s established policy.Journal of Scientific Research17 March 2012 doi: http://dx.doi.org/10.3329/jsr.v4i1.7598J. Sci. Res. 4 (1), 251-262 (2012)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…For the non-germinated samples, 50 g rice grains were washed, dried, ground (200–300 µm), and stored using the same method described above for the germinated grains. Both the germinated and non-germinated rice samples were analyzed for their bioactive compounds γ-oryzanol, GABA, phytic acid, tocols (tocopherols and tocotrienols), and policosanol, based on previously described methods [22,23,24,25,26] and for their proximate compositions using the methods of AOAC [27]. The results are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For the non-germinated samples, 50 g rice grains were washed, dried, ground (200–300 µm), and stored using the same method described above for the germinated grains. Both the germinated and non-germinated rice samples were analyzed for their bioactive compounds γ-oryzanol, GABA, phytic acid, tocols (tocopherols and tocotrienols), and policosanol, based on previously described methods [22,23,24,25,26] and for their proximate compositions using the methods of AOAC [27]. The results are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…It can be seen that there was a decreasing trend on the hydration properties of the flour (WBC, WHC and SV) as germination time increased, although that decrease was only significant in the case of WBC. During germination, enzyme activities like the α-amylase increases, which led to starch degradation and subsequent increase of small dextrins and fermentable sugar (Islam and Becerra 2012). The starch degradation might induce the release of the water entrapped within the starch granule, and that effect was even more dramatic as the starch hydrolysis proceeds and thus at extended germination, reducing the flour hydration properties.…”
Section: Flour and Flour Gel Hydration Propertiesmentioning
confidence: 99%
“…Biochemical changes occur during germination of rice which causes softening of the endosperm and an increase in nutrient bioavailability (Islam and Becerra, 2012;Patil and Khan, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The rice is considered germinated when the primary root is already visible (Moongngarm and Khomphiphatkul, 2011). A number of studies have shown that germinated rice possesses various pharmacological properties, such antidiabetic, antihyperlipidemia, antioxidant, and anticancer (Mohd Esa et al, 2013;Patil and Khan, 2011;Wu et al, 2013b).Biochemical changes occur during germination of rice which causes softening of the endosperm and an increase in nutrient bioavailability (Islam and Becerra, 2012;Patil and Khan, 2011).Pigmented rice varieties are rice grains with colored pericarp and have been shown to have higher amounts of nutrients and greater antioxidant capacity than ordinary non-pigmented rice (Laokdiluk et al, 2011;Kang et al, 2013). A study conducted by Nam et al (2005) revealed that extracts from pigmented rice brans have anticancer and antimutagenic properties.…”
mentioning
confidence: 99%